Association between the Wilms tumor-1 rs16754 polymorphism and acute myeloid leukemia: A MOOSE-compliant meta-analysis. Issue 27 (2nd July 2020) - Yu, Xin; Zhang, Yuan; Liu, Shuang; Mu, Yu; Shang, Fengjia; Zhang, Nan
Abstract : Abstract: The Wilms tumor-1 (WT1) protein is an important regulator of malignant hematopoiesis and has been implicated in the pathogenesis of acute myeloid leukemia (AML). Recently special attention has been paid to the relationship of the WT1 single nucleotide polymorphism (SNP) rs16754 with AML risk and outcome, but the conflicting results made it difficult to draw definitive conclusions. In the present study, we systematically reviewed the literature and performed a meta-analysis of existing evidence. We searched Embase, Pubmed, Web of Science, Medline, Cochrane Library, Wanfang, and China National Knowledge Infrastructure databases using predefined search methodology for relevant studies. We pooled odd ratio (OR) with 95% confidence intervals (95% CI) to evaluate the association between SNP rs16754 and AML risk. In addition, we analyzed hazard ratio (HR) with 95% CI for overall survive, relapse-free survival, and disease-free survival. Q-statistic was used to assess the homogeneity and Egger test was used to evaluate publication bias. Eleven studies met the inclusion criteria for analysis. The results of fixed-effect meta-analyses revealed no association between SNP rs16754 and AML risk (AA + GA vs GG: OR = 0.92, 95% CI: 0.71–1.19, P = .518; AA vs GA + GG: OR = 1.23, 95% CI: 0.86–1.76, P = .262; AA vs GG: OR = 1.05, 95% CI: 0.68–1.63, P = .820; AG vs AA: OR = 0.77, 95% CI: 0.53–1.13, P = .186; AG vs GG: OR = 0.89, 95% CI: 0.68–1.16, P = .376). In subgroup analysis by race, age, and disease type, we did not find any significant association. However, the presence of rs16754 GA/GG genotype was associated with improved overall survive (HR = 0.48, 95% CI: 0.26–0.91, P = .024) and relapse-free survival (HR = 0.82, 95% CI: 0.68–1.00, P = .048) compared with the rs16754 AA. In summary, the WT1 SNP rs16754 was not associated with AML risk, but it had a significant impact on clinical outcome in AML patients.